New hybrid approach for identification of spermatozoa in human semen sample using microscope image processing techniques - Chaudhari, Nandini Mukund; Pawar, Bhausaheb V. (European Journal of Applied Sciences, 2015)
Due to very hectic, stressful and exhaustive life style, Today, Infertility is a common problem in most of the couples and they have to undergo for intrauterine insemination (IUI) or In-vitro fertilization (IVF). Semen analysis is fundamental test in the clinical work up of the infertile male. Computerized semen test will give many more & accurate parameters that are useful to the fertility specialist. This paper focuses on finding the numbers of spermatozoa contain in the semen sample with new hybrid approach using MATLAB. Use of background subtraction is the first stage of algorithm. Region based segmentation finds the numbers of sperm in the semen sample. The comparative analysis of segmentation shows that region base segmentation detects more objects. So it is possible to find the suppressed (low intensity) sperm in given frame.